Efektivitas Sediaan Sabun Wajah Cair Ekstrak Daun Katuk (Sauropus androgynus (L.) Merr.) terhadap Pertumbuhan Bakteri Staphylococcus aureus Metode Difusi - Salim, Maulidiyah; Gestiwana, Oksa; Kamilla, Laila (Jurnal Laboratorium Khatulistiwa, 2023)
Sweet leaf bush are one of the vegetable plants that are rich in nutrients and secondary metabolites, so they are commonly used as vegetables and as herbal medicines. The results of the phytochemical screening of sweet leaf bush contain tannins, saponins, flavonoids and alkaloids, so that sweet leaf bush can be used as an antibacterial liquid facial soap preparation. This study aims to determine the effectiveness of liquid facial soap preparations of sweet leaf bush extract formula I with a concentration of 5%, formula II with a concentration of 10%, formula III with a concentration of 15% and formula IV with a concentration of 20% in inhibiting the growth of Staphylococcus aureus bacteria using the diffusion method.This research design uses Quasi Experiment. The population in this research is sweet leaf bush. The sample used was sweet leaf bush extract which was used to make antibacterial liquid facial soap preparations with formula I of 5% concentration, formula II with a concentration of 10%, formula III with a concentration of 15% and formula IV with a concentration of 20%. Antibacterial testing method using the Kirby-Bauer diffusion method.The results of the antibacterial study obtained an average diameter of the inhibition zone in formula I of 12,167 mm, formula II of 14,667 mm, formula III of 17,083 mm and formula IV of 18,667 mm. Based on the diameter of the inhibition zone formed in formulas I, II, III and IV it is categorized as a strong inhibition response.The results of the statistical analysis of the One Way Anova test obtained p value = 0.000 < α 0,05, which means that there is a difference between the average concentrations of the sweet leaf bush extract liquid face soap formula in inhibiting the growth of Staphylococcus aureus bacteria using the diffusion method.Sweet leaf bush are one of the vegetable plants that are rich in nutrients and secondary metabolites, so they are commonly used as vegetables and as herbal medicines. The results of the phytochemical screening of sweet leaf bush contain tannins, saponins, flavonoids and alkaloids, so that sweet leaf bush can be used as an antibacterial liquid facial soap preparation. This study aims to determine the effectiveness of liquid facial soap preparations of sweet leaf bush extract formula I with a concentration of 5%, formula II with a concentration of 10%, formula III with a concentration of 15% and formula IV with a concentration of 20% in inhibiting the growth of Staphylococcus aureus bacteria using the diffusion method.This research design uses Quasi Experiment. The population in this research is sweet leaf bush. The sample used was sweet leaf bush extract which was used to make antibacterial liquid facial soap preparations with formula I of 5% concentration, formula II with a concentration of 10%, formula III with a concentration of 15% and formula IV with a concentration of 20%. Antibacterial testing method using the Kirby-Bauer diffusion method.The results of the antibacterial study obtained an average diameter of the inhibition zone in formula I of 12,167 mm, formula II of 14,667 mm, formula III of 17,083 mm and formula IV of 18,667 mm. Based on the diameter of the inhibition zone formed in formulas I, II, III and IV it is categorized as a strong inhibition response.The results of the statistical analysis of the One Way Anova test obtained p value = 0.000 < α 0,05, which means that there is a difference between the average concentrations of the sweet leaf bush extract liquid face soap formula in inhibiting the growth of Staphylococcus aureus bacteria using the diffusion method.